FASER experiment and first results from LHC run 3 - Umut Kose, on behalf of FASER collaboration (SciPost Physics Proceedings)
FASER is designed to search for light, extremely weakly interacting and long-lived beyond standard model particles at the CERN Large Hadron Collider. Such particles, e.g., dark photons, may be produced in the high-energy proton-proton collisions at the ATLAS interaction point and then decay to visible particles in FASER, which is placed 480 m downstream and aligned with the collision axis line-of-sight. The detector covers a previously unexplored range of pseudorapidity larger than 8.8, which allows it to have sensitivity to new physics in the far-forward region. FASER also has a sub-detector called FASER$ν$, which is specifically designed to detect and investigate high-energy collider neutrino interactions in the TeV regime, extending current cross-section measurements. In this proceeding, the FASER detector and present recent results obtained during LHC Run 3 will be introduced.